Kissing-Y stenting for endovascular treatment of complex wide necked bifurcation aneurysms using Acandis Acclino stents: results and literature review. (18th May 2015) - Brassel, Friedhelm; Melber, Katharina; Schlunz-Hendann, Martin; Meila, Dan
Abstract : Introduction: Y-configured stent assisted coiling is a promising therapeutic option to ensure safe coil embolization and preserve the affected arteries in complex wide necked aneurysms. We present our experience with self-expanding Acandis Acclino stents for the treatment of complex aneurysms using the kissing-Y technique. Methods: We retrospectively reviewed seven patients with seven complex aneurysms (three anterior communicating artery (AcomA), two middle cerebral artery, one basilar artery/superior cerebellar artery, and one vertebral artery/posterior inferior cerebellar artery) who were treated with the kissing-Y technique by stent assisted coiling from June 2013 to July 2014, with follow-up until January 2015. DSA follow-up was up to 17 months, with a mean follow-up period of 10 months. Six patients were treated electively and one in the acute phase of a subarachnoid hemorrhage. In all cases, closed cell Acandis Acclino stents were used. We evaluated procedural complications, clinical outcomes, and mid term angiographic follow-up. Additionally, a literature review is provided. Results: In all patients, stents were successfully placed and implanted. One patient developed a periprocedural thromboembolic complication not directly related to the stents. No other periprocedural or postprocedural complications were encountered. Follow-up examinations showed stable and total occlusion of all coiled aneurysms. Conclusions: The results of our study show that the kissing-Y technique using closed cell Acandis Acclino stents followed by coil embolization is a feasible treatment option for selected complex bifurcation aneurysms.